Building religious, honesty, discipline and student curiosity characters in online HOTS-based citizenship education learning - Chotimah, Umi; Kurnisar, Kurnisar; Ermanovida, Ermanovida; Juainah, Norma (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This article aims to describe the efforts to build religious, honesty, discipline, and student "˜s curiosity characters through HOTS-based online Civics learning. The implementation uses a qualitative approach with the case study method, which is implemented in the Indralaya class Civics learning process. Data were collected through observation, interviews, and documentation, then analyzed using three stages from Miles & Huberman, namely data reduction, data display and data verification/conclusion. The results show that building religious , honesty, discipline, and student curiosity characters in HOTS-based Civics learning can be pursued even though the implementation is online learning system. This character development is carried out through various activities, starting from planning, implementing student-oriented learning, and comprehensive assessment. However, this does not mean that apart from the four characters, there is no need to develop other characters. It means that other characters are still built but in line with each learning outcomes and each meeting's subject matter.